(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Transitioning from traditional advertising techniques to highly personalized digital campaigns, the healthcare sector has seen a paradigm change in marketing strategy. This study examines the development of digital marketing inside the healthcare enterprise, emphasizing patron involvement, facts-driven customisation, and the efficacy of on-line platforms. The research, which has 200 respondents as its sample size, looks at important variables affecting the uptake and effectiveness of digital marketing in the healthcare industry. While demographic data offers insights into the various types of healthcare consumers, quantitative data analysis investigates the preferences of patients and healthcare professionals. The results demonstrate the expanding significance of AI-powered and consumer data-driven personalized marketing in elevating patient engagement, boosting healthcare outcomes, and propelling agency growth.